1999
DOI: 10.1016/s0140-6736(99)01306-9
|View full text |Cite
|
Sign up to set email alerts
|

Visceral pain

Abstract: Visceral pain is the most common form of pain produced by disease and one of the most frequent reasons why patients seek medical attention. Yet much of what we know about the mechanisms of pain derives from experimental studies of somatic not visceral nociception. The conventional view is that visceral pain is simply a variant of somatic pain, a view based on the belief that a single neurological mechanism is responsible for all pain. However, the more we learn about the mechanisms of somatic and visceral pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
304
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(322 citation statements)
references
References 26 publications
4
304
0
11
Order By: Relevance
“…It is also suggested that visceral pain has a long time of onset and that it is much more prevalent at 10 and 15 years after injury than during the early course of the injury. 12,13 Visceral pain has been described or defined as being dull, poorly localized, bloating and cramping, 15,16 but no study has examined the characteristics of visceral pain in SCI in more detail. Also, little is known about the possible predictors of visceral pain.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that visceral pain has a long time of onset and that it is much more prevalent at 10 and 15 years after injury than during the early course of the injury. 12,13 Visceral pain has been described or defined as being dull, poorly localized, bloating and cramping, 15,16 but no study has examined the characteristics of visceral pain in SCI in more detail. Also, little is known about the possible predictors of visceral pain.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with visceral pain often exhibit a wide variety of somatic symptoms including back pain, migraine headaches, and muscle pain. These symptoms may be consistent with central sensitization; referral of visceral pain to somatic tissues outside the area of immediate referral [1][2][3][4][5] or neural cross-talk in which afferent activation of one visceral structure influences efferent output in other structures and organs and is mediated by convergence of sensory pathways in the spinal cord [6][7][8][9][10].. Somatic hypersensitivity may also occur in clinical conditions where visceral pain is directly referred to a corresponding area of somatic tissue. Referred visceral hypersensitivity is most often related to visceral pain being directly referred to the corresponding area of the abdominal wall [2,11, and 12].…”
Section: Introductionmentioning
confidence: 99%
“…At present, one of the leading hypotheses regarding the origin of symptoms in IBS is provided by the concept of visceral hypersensitivity. 3,4 In this view, hypersensitivity of the gut may lead to alterations in gut motility by altering regulatory reflex pathways and secretory functions, which in turn may lead to functional disturbances. In addition, normal, physiologic stimuli may be perceived with increased intensity or may even cause pain.…”
Section: Introductionmentioning
confidence: 99%